2018
DOI: 10.1038/s41598-017-18361-3
|View full text |Cite
|
Sign up to set email alerts
|

Piperonylic acid stimulates keratinocyte growth and survival by activating epidermal growth factor receptor (EGFR)

Abstract: Epidermal growth factor (EGF) stimulates cell growth, proliferation, and survival. The biological benefits of EGF have been utilized in medical uses for improving wound healing as well as in today’s skin cosmetics. EGF has been found in urine, saliva, milk, and plasma, but its efficient isolation remains a difficult task. With technical advances, recombinant protein purification technique has been used for EGF production. However, the recombinant EGF is still expensive and keeping it with stable activity is di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…We demonstrated that PA improved wound healing, providing a better-quality scar with characteristics closer to uninjured skin. Previous data in the literature [ 10 ] and the results of this study suggest that these events occur through the activation of EGFR, which is a component of the EGF family and is predominantly distributed in keratinocytes [ 9 ]. EGFR knockout mice present a serious impairment of the healing process, with delayed wound closure accompanied by a decrease in keratinocyte migration and increased edema [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…We demonstrated that PA improved wound healing, providing a better-quality scar with characteristics closer to uninjured skin. Previous data in the literature [ 10 ] and the results of this study suggest that these events occur through the activation of EGFR, which is a component of the EGF family and is predominantly distributed in keratinocytes [ 9 ]. EGFR knockout mice present a serious impairment of the healing process, with delayed wound closure accompanied by a decrease in keratinocyte migration and increased edema [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 53%
“…We first carried out a dose-response experiment to determine which dose of PA to use, based on the concentration of 100 μM used in a previous study in cultured keratinocytes [ 10 ]. For this, we used 20 C57BL/6 mice randomly divided into four groups: vehicle, 10 mM PA, 1 mM PA, and 100 μM PA. Each mouse was treated daily until day 9 post-injury.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of His-hSCF248 on the TF-1 cell proliferation is 400-fold stronger than that of commercial hSCF189 in terms of molar concentration. The hSCF164 induces gene expression regulation related to cell growth by activating the c-Kit receptor and downstream signaling pathway [34][35][36]. His-hSCF248 demonstrated strong activity at 1000-fold lower concentration than hSCF164 in c-Myc mRNA expression, doubling time, and cell cycle.…”
Section: Discussionmentioning
confidence: 99%